2005
DOI: 10.1175/bams-86-9-1275
|View full text |Cite
|
Sign up to set email alerts
|

THE I3RC: Bringing Together the Most Advanced Radiative Transfer Tools for Cloudy Atmospheres

Abstract: An international Intercomparison of 3D Radiation Codes (I3RC) underscores the vast progress of recent years, but also highlights the challenges ahead for routine implementation in remote sensing and global climate modeling applications. Modeling atmospheric and oceanic processes is one of the most important methods of the earth sciences for understanding the interactions of the various components of the surface-atmosphere system and predicting future weather and climate states. Great leaps in the availability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
172
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 208 publications
(176 citation statements)
references
References 48 publications
4
172
0
Order By: Relevance
“…The delta-Eddington solution is applied in every column using the local cloud optical depth. A study by de Roode and Los (2008) of the cloud albedo bias effect showed a good agreement between results obtained with the delta-Eddington approach and from the I3RC Monte-Carlo model (Cahalan et al, 2005) that utilizes the full three-dimensional structure of the cloud field.…”
Section: The Delta-eddington Model For Shortwave Radiative Transfermentioning
confidence: 60%
“…The delta-Eddington solution is applied in every column using the local cloud optical depth. A study by de Roode and Los (2008) of the cloud albedo bias effect showed a good agreement between results obtained with the delta-Eddington approach and from the I3RC Monte-Carlo model (Cahalan et al, 2005) that utilizes the full three-dimensional structure of the cloud field.…”
Section: The Delta-eddington Model For Shortwave Radiative Transfermentioning
confidence: 60%
“…SHDOM is more computationally efficient compared to Monte Carlo (MC) methods when solving the whole-sky radiance field. SHDOM is also found to be within 2-3 % (close to the noise level) of the MC models in the intercomparison of 3-D radiation codes (I3RC) Cahalan et al, 2005). Because of its computational efficiency and accuracy, SHDOM is selected for this analysis.…”
Section: Shdom Model and Input Parametersmentioning
confidence: 82%
“…In addition to these the uvspec model has also successfully participated in a model comparison of UV-indices and the Intercomparison of 3-D Radiation Codes (Cahalan et al, 2005).…”
Section: Model Validationmentioning
confidence: 99%
“…Second, the threedimensional distribution of liquid water content and droplet or particle size. To demonstrate the treatment of inhomogeneous clouds in libRadtran we chose the second case of the Intercomparison of 3-D Radiation codes (Cahalan et al, 2005). The two-dimensional cloud field is based on extinction retrievals from the MMCR (Millimeter Cloud Radar) and the MWR (microwave radiometer) at the ARM CART site in Oklahoma on 8 February 1998.…”
Section: Inhomogeneous Clouds (Uvspec)mentioning
confidence: 99%